Study on the Development and Use of E-commerce in the Special Region of Yogyakarta with De Lone and Mc. Lean IS Success Model - Kairupan, Daniel; Badrudin, Rudy; Dodo, Yakobu Aminu (KINERJA, 2022)
The high growth of e-commerce in Indonesia is influenced by several things. Because of changes in people's behavior and the advancement of the quality of information and the quality of services. This includes the Special Region of Yogyakarta (DIY), which is one of the areas with the highest level of e-commerce service users in Indonesia. This research was conducted to study the development and use of e-commerce in the Special Region of Yogyakarta (DIY). This needs to be done because even though DIY is one of the areas with the highest level of e-commerce service users in Indonesia, the level of e-commerce business activity in Indonesia, especially DIY, is still relatively new, so there are still many shortcomings in its implementation. Researchers use e-commerce metrics suggested by DeLone and Mc.Lean (2004) as the foundation of the instrument. Research data processing using Smart Partial Least Square (Smart-PLS) 3.0. The analytical model used in this study is a structural equation model (SEM) and inductive analysis using goodness of fit model (inner model) research which serves to determine the suitability of a model used in this study. From the data processing that has been done, there are 2 independent variables that have no significant effect on the dependent variable. From this finding it is expected that companies engaged in e-commerce services can focus on achieving net benefits by paying attention to several variables that have a significant influence. The findings of this study also support several previous studies that have been tested previously.